Towards Integrated Facility-Wide Data Acquisition and Analysis at NSLS-II. Issue 2 (4th March 2017) - Arkilic, A.; Allan, D. B.; Caswell, T.A.; Li, L.; Lauer, K.; Abeykoon, S.
Abstract : The National Synchrotron Light Source II (NSLS-II) is the newest, highly optimized third-generation synchrotron facility in the world. NSLS-II accommodates a wide range of scientific research, from materials and energy science to biological applications, which take advantage of its unprecedented brightness, photon flux, and beam stability in infrared, soft and hard X-rays. New X-ray facilities like NSLS-II provide brighter beams than their predecessors, and new X-ray detectors have been built to take advantage of those higher-intensity beams. As a result, acquisition rates and detector sizes have dramatically increased. Both the raw volume of data to process and the metadata to organize it present new challenges. The technology to acquire, manage, and make full scientific use of this data is just emerging.